Applications of Stimuli-Responsive Hydrogels in Bone and Cartilage Regeneration - Xiaoqi Ni; Xin Xing; Yunfan Deng; Zhi Li (MDPI AG, 2023)
Bone and cartilage regeneration is an area of tremendous interest and need in health care. Tissue engineering is a potential strategy for repairing and regenerating bone and cartilage defects. Hydrogels are among the most attractive biomaterials in bone and cartilage tissue engineering, mainly due to their moderate biocompatibility, hydrophilicity, and 3D network structure. Stimuli-responsive hydrogels have been a hot topic in recent decades. They can respond to external or internal stimulation and are used in the controlled delivery of drugs and tissue engineering. This review summarizes current progress in the use of stimuli-responsive hydrogels in bone and cartilage regeneration. The challenges, disadvantages, and future applications of stimuli-responsive hydrogels are briefly described.